Green Tea Epigallocatechin 3-Gallate Reduced Platelet Aggregation and Improved Anticoagulant Proteins in Patients with Transfusion-Dependent β-Thalassemia: A Randomized Placebo-Controlled Clinical Trial - Touchwin Petiwathayakorn; Sasinee Hantrakool; Kornvipa Settakorn; Nuntouchaporn Hutachok; Adisak Tantiworawit; Nopphadol Chalortham; Pimpisid Koonyosying; Somdet Srichairatanakool (Foods)
Patients with transfusion-dependent β-thalassemia (TDT) with iron overload have been linked to hypercoagulability and increased platelet (PLT) activation that causes thrombosis. Green tea extract (GTE) rich in epigallocatechin-3-gallate (EGCG) exerts iron-chelating and antithrombotic properties. The study aimed to assess the effects of GTE treatment on plasma coagulation state and PLT function in vitro and in patients with TDT. The subjects consumed a placebo or GTE tablets (50 mg and 2 × 50 mg EGCG equivalent) every day for two months. Blood was then collected from the treated patients for analyses of PLT numbers, agonist-induced PLT aggregation, and anti-coagulation proteins. In our findings indicate that the in vitro treatment of GTE (at least 1 mg EGCG equivalent) inhibited PLT aggregation in patients who were healthy and with thalassemia platelet-rich plasma (PRP), which was significant in the healthy PRP. Consistently, GTE treatment inhibited the PLT aggregation that had been ex vivo generated by collagen or ADP. In addition, consumption of GTE tablets greatly inhibited PLT aggregation and increased the plasma levels of proteins C and S, as well as the free protein S concentrations depending upon the time course, but not the GTE dosage. Moreover, plasma ferritin levels decreased in both green tea tablet groups in a time-dependent manner (p < 0.05 in the second month). In conclusion, EGCG-rich GTE diminished PLT aggregation in patients who were healthy and patients with thalassemia plasma. It also improved PLT aggregation and hypercoagulability in patients with TDT by increasing the antithrombotic activity of protein C and protein S. This would suggest an adjuvant of GTE could reduce the risk of thrombosis associated with iron overload.